BM ORI: SEARCH FOR SECONDARY SPECTRAL LINES - Shevchenko, V. S.; Vitrichenko, E. A. (Одеські астрономічні публікації, 2017)
The search for the secondary spectral lines was made by using special high signal/noise ratio emulsion A700u. The four spectra (two near elongations and two near conjunctions) were obtained with 6-m telescope (BTA), dispersion is 26 Å/mm. We searched the weak lines and made the next conclusions. The following splitted stellar lines are seen: 0 II 4699, Mg II 4481, Si IV 4116, N II 5747, N II 5001, N II 5747 and others. The contours of these lines are complex: each have absorption contour, emission core and an Orion nebulae emission line. It made difficult the line recognition. Also are seen the splitted circum-stellar lines Na I 5890 and 5896 with the same radial velocities as stellar lines. If that fact is real the next parameters of the system may be derived: K1 = 156 km/s, K2 = 232 km/s, so the mass ratio M1/M2 = 1.5 and M1 = 24, M2 = 15 M☉ radii of the primary and secondary are 4 and 13 R☉. The errors may be about 10%. Both stars are of B2 spectral type, both are surrounded by gas/dust envelopes but the secondary has more opaque dust envelope and that produces the reddening about 0.3 optical thickness greater then for the primary. That is the reason of the different minima depth for the different spectral regions. All results are preliminary and are to be confirmed.